Phytosynthesis of CuONPs viaLaurus nobilis: Determination of antioxidant content, antibacterial activity, and dye decolorization potential - Bulut Kocabas, Buket; Attar, Azade; Peksel, Aysegul; Altikatoglu Yapaoz, Melda (WILEY, 2021)
Copper oxide nanoparticles (CuONPs) were phytosynthesized byLaurus nobilisleaf extract, which was used as a reducing and capping agent. UV-vis spectroscopy was applied, and the spectrum of CuONPs gave a peak around 300 and 325 nm. An intense Fourier transform infrared spectroscopy between 4000 and 500 cm(-1)wavelengths exhibited exterior functional groups of CuONPs. The results of scanning electron microscopy and transmission electron microscopy revealed that the green synthesized CuONPs were spherical in shape with sizes between 90 and 250 nm. Antibacterial activity of CuONPs was evaluated against both Gram-positive and Gram-negative bacteria. Brilliant Blue R-250 was employed in the dye decolorization studies, and CuONPs achieved 69% decolorization in 60 Min. The antioxidant activity of CuONPs was calculated by analyzing total phenolic compounds and flavonoid content. Furthermore, the reducing power of extract and nanoparticles was determined. Total phenolic compounds of CuONPs were determined as 6.7 mu g of pyrocatechol equivalent/mg, while total flavonoids were measured as 236.62 mu g catechin/mg sample. Results indicated that the method of CuONP formation is simple and low cost and the phytosynthesized CuONPs had antibacterial, antioxidant, and dye decolorization activity.
Keywords: antibacterial activity; antioxidant activity; copper oxide nanoparticles; dye decolorization; Laurus nobilis; phytosynthesis; GREEN SYNTHESIS; OXIDE NANOPARTICLES; SILVER NANOPARTICLES; LEAF EXTRACT; L. LEAVES; PHENOL; GOLD; BLUE; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology